Risk Factors for Urinary Tract Infection in Hospitalized Patients - Hadiati Setyorini; Nunuk Mardiana; Artaria Tjempakasari (Biomolecular and Health Science Journal, 2019)
Introduction: Urinary tract infection (UTI) is the most common infection that can be fatal and has higher rate mortality especially in some patient. This study is aim to analyze risk factors for urinary tract infection in hospitalized patients for prevention and more aggressive approach can be taken.Methods: Consecutively, medical records of 285 patients with urinary analysis was recorded for risk factors and urine culture results if suspected UTI. Risk factors for sex, age, urinary catheter, urolithiasis, DM, and immobilization was analyzed with bivariate analysis and multivariate analysis.Results: From 285 patients, 92 patients had UTI with average age was 52.45 years old, 48 (56.49%) were female. Most common pathogen were E. coli (41.3%), Enterobacter sp. (8.8%) and Enterococcus faecalis (7.6 %). From bivariate analysis, geriatric age (>60 years) has RR 1.421 (95% CI 1.015-1.989, p=0.046) and immobilization has RR 1.861 (95% CI 1.266-2.738, p=0.007), whereas sex (RR 1.190 95% CI 0.851 – 1.664, p=0.310), diabetes (RR 1.171 95% CI 0.833 – 1.645, p=0.367), insulin usage (RR 0.900 95% CI 0.519 – 1.561, p= 0.703), glycosuria (RR 1.152 95% CI 0.741 – 1.791, p=0.522), and CKD (RR 1.475 95% CI 0.896 – 2.430, p= 0.126) give insignificant result. From multivariate analysis, urinary catheter has OR 4.506 (95% CI 2.312-8.872, p=0.000), urolithiasis with OR 4.970 (95% CI 1.931-12.787, p=0.001), and hyperglycemia has OR 2.871 (95% CI 1.485-5.551, p=0.002).Conclusion: Geriatric age and immobilization are risk factors for urinary tract infection, and urinary catheter, urolithiasis, and hyperglycemia are independent risk factors for urinary tract infection.